1993
DOI: 10.1128/iai.61.6.2390-2395.1993
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and efficacy of oral or intranasal Shigella flexneri 2a and Shigella sonnei proteosome-lipopolysaccharide vaccines in animal models

Abstract: Immunity against shigellosis has been shown to correlate with the presence of antibodies specific for Shigella lipopolysaccharide (LPS). We here propose a new candidate vaccine for shigellosis composed of purified Shigella flexneri 2a or Shigella sonnei LPS hydrophobically complexed with group C type 2b Neisseria meningitidis outer membrane protein proteosomes. Immunization of mice either orally or intranasally with this complex induced specific homologous anti-LPS antibodies in both intestinal and respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…Intranasal immunization. On days 0 and 7, groups of fifteen mice were given 100 µg of CE or veronal buffer (control) in 20 111 volumes (29). Two micrograms of cholera toxin (CT) (from Vibrio cholerae type Inaba 5898, Calbiochem 227035) were added to the first dose.…”
mentioning
confidence: 99%
“…Intranasal immunization. On days 0 and 7, groups of fifteen mice were given 100 µg of CE or veronal buffer (control) in 20 111 volumes (29). Two micrograms of cholera toxin (CT) (from Vibrio cholerae type Inaba 5898, Calbiochem 227035) were added to the first dose.…”
mentioning
confidence: 99%
“…The studies showed that OMVs could not only be combined with proteins but also with other components. The study showed that meningitides-derived OMVs can be complexed with Shigella-specific LPS to provide the immunity against Shigella keratoconjuctivitis (Orr, Robin, Cohen, Arnon, & Lowell, 1993). Another study showed that when combined with inactivated respiratory syncytial virus (iRVS), N. meningitidis OMVs enhanced the protective immunity (Etchart et al, 2006).…”
Section: Omvs In Vaccinationmentioning
confidence: 99%
“…Six weeks prior to infection, mice received CVD 1208S-122 or the vector intranasally (10 6 CFU/ mouse in 10 µL of saline) in three weekly doses. We used intranasal route due to vast evidence in the literature indicating its effective immunogenicity for shigellosis and other enteric infections 20,21 . In order to allow development of antibody production, we performed challenge infections 4 weeks after the last immunization.…”
Section: Cvd 1208s-122 Vaccine and Immunization Protocolmentioning
confidence: 99%